DYNAMICS OF MORBIDITY OF THE WEST NILE FEVER IN THE ASTRAKHAN REGION - S. F. Karpenko; Kh. M. Galimzyanov; B. I. Kantemirova; R. S. Arakelyan; A. R. Kurbangalieva; G. L. Shendo (Инфекция и иммунитет, 2018)
.